Common Kyushu-Ryukyuan substratum in maritime vocabulary: A preliminary analysis - Jarosz, Aleksandra; Orlandi, Georg (Lingua Posnaniensis, 2023)
This paper constitutes a preliminary linguistic test of the hypothesis which postulates that shared Kyushu-Ryukyuan lexicon related to maritime knowledge provides evidence for a Kyushu-Ryukyuan subgrouping within the Japonic cladogram. The paper introduces Kyushu-Ryukyuan cognates and potential shared lexical innovations in seafaring vocabulary, cardinal directions and navigation, and marine fauna, all of which suggest a shared Kyushu-Ryukyuan navigation culture, as well as common maritime subsistence and lifestyle patterns. The case is reinforced by several promising cases of common morphological features between Kyushu and Ryukyuan. The overall conclusion is that the compared linguistic data does support the Kyushu-Ryukyuan clade. Finally, we identify a mismatch between lexical and morphological evidence concerning lower-unit classification of the South Japonic node. We observe that while shared innovative vocabulary allows to postulate Proto-Satsugū-Ryukyuan within Kyushu-Ryukyuan as the most direct mainland ancestor of Ryukyuan languages – the predecessor pre-Proto-Ryukyuan language that was still spoken in Kyushu in the first millennium AD – shared grammatical features do not suggest any particular subdivision of Kyushu-Ryukyuan.